Relationship Between Health Belief Factors And Behavior Wound Care In The Elderly - Namnoer, Jitra; Akaratanapol, Prisana; Khungtumneam, Kamontip (Journal of The Royal Thai Army Nurses, 2025)
This descriptive research aimed to study the relationship between health beliefs and wound care behaviors of the elderly. The sample consisted of 70 elderly with a history of open wounds who were treated as outpatients at Phanomsarakham Hospital, Chachoengsao Province, and had a follow-up appointment 1 week after the wound occurred. Data were collected using the Wound Care Behaviors of the Elderly Questionnaire and the Relationship between Health Beliefs and Wound Care Behaviors of the Elderly Questionnaire. The questionnaire was examined for content validity by 3 experts. The content validity (CVI) was between 0.89 and 0.97, and the Cronbach’s alpha coefficients were 0.72 and 0.93, respectively. The data were analyzed using descriptive statistics and Pearson’s product moment correlation coefficient. The results of the research found that the wound care behavior of the elderly was at a good level overall ( = 2.33, SD = 0.54). Factors related to wound care behavior of the elderly were : Perceived risk of wound infection (r = 0.73, p<.05), perceived severity of wound infection (r = 0.44, p<.01), perceived benefits of wound care (r = 0.68, p<.05), and perceived barriers to wound care were negatively related to wound care behavior of the elderly (r = -0.45, p<.05).